RACISM AND ALGORITHMS IN THE 2024 ELECTIONS: THE CHALLENGE FACED BY BLACK AND BROWN CANDIDATES ON SOCIAL MEDIA: O DESAFIO DOS CANDIDATOS PRETOS E PARDOS NAS REDES SOCIAIS - Oliveira, Isadora Sant’Ana de; Brito, LucianaHelena da Silva; Braga, Sabrina de Paula (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
This article examines the risks posed by algorithmic racism to the political sphere, with particular emphasis on its impact on the candidacies of Black and Brown individuals in the 2024 Brazilian municipal elections. The increasing influence of algorithms has led social media and digital platform users to accept algorithmically curated content as unquestionable truths, despite the presence of systemic biases. Within this context, manifestations of racism have intensified, as reflected in data from Safernet, which reported a significant rise in complaints of racist incidents on Brazilian social media in 2023. This study aims to analyze the electoral campaigns of mayoral candidates in the cities of São Luís (MA), Belo Horizonte (MG), and Fortaleza (CE) through the lens of Instagram, investigating potential factors behind the disparities observed between white and Black candidates. The findings highlight how the algorithm-driven dynamics of digital media can foster underrepresentation and create additional barriers for marginalized groups in the political process. By advancing these discussions, this research seeks to contribute to the development of strategies and policy interventions capable of mitigating algorithmic distortions that exacerbate polarization and disproportionately affect democratic participation in Brazil.